PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE ANDROID DI FAKULTAS EKONOMI UNIVERSITAS KRISNADWIPAYANA - Muhammad Luthfi Rifa’i; Wiwik Rachmarwi (Jurnal Ekonomi dan Industri, 2025)
The purpose of this study is to determine the extent to which product quality and promotion influence partially and simultaneously on the purchase decision of android mobile phones of students in the Faculty of Economics, Krisnadwipayana University. This study uses a quantitative approach. Data collection was carried out by distributing questionnaires to students of the Faculty of Economics, Krisnadwipayana University. The analysis used in this study is descriptive analysis and multiple linear regression. The results of the study concluded that quality and promotion have a significant influence partially and simultaneously on the purchase decision of Android mobile phones among students.